Screening of Bovine Tissue-Specific Expressed Genes and Identification of Genetic Variation Within an Adipose Tissue-Specific lncRNA Gene - Zhang, Sihuan; Xu, Han; Jiang, Enhui; Akhatayeva, Zhanerke; Jiang, Fugui; Song, Enliang; Pan, Chuanying; Chen, Hong; Lan, Xianyong (Frontiers in Veterinary Science, 2022)
Global classification of bovine genes is important for studies of biology and tissue-specific gene editing. Herein, we classified the tissue-specific expressed genes and uncovered an important variation in the promoter region of an adipose tissue-specific lncRNA gene. Statistical analysis demonstrated that the number of genes specifically expressed in the brain was the highest, while it was lowest in the adipose tissues. A total of 1,575 genes were found to be significantly higher expressed in adipose tissues. Bioinformatic analysis and qRT-PCR were used to uncover the expression profiles of the 23 adipose tissue-specific and highly expressed genes in 8 tissues. The results showed that most of the 23 genes have higher expression level in adipose tissue. Besides, we detected a 12 bp insertion/deletion (indel) variation (rs720343880) in the promoter region of an adipose tissue-specific lncRNA gene (LOC100847835). The different genotypes of this variation were associated with carcass traits of cattle. Therefore, the outcomes of the present study can be used as a starting point to explore the development of cattle organs and tissues, as well as to improve the quality of cattle products.